Simplified control system for grid-tied modular multilevel based energy storage - Nikita Dobroskok; Viktor S. Lavrinovskiy; Ekaterina S. Trusova (Institute of Advanced Engineering and Science, 2023)
Microgrids and networks with renewable energy sources are increasingly common. A network energy storage device is required for their normal operation. Common high-voltage storage devices have many disadvantages. It may create a risk of fire or electric shock if it is not handled carefully. It is not possible to utilize used batteries both safely and effectively at the same time. Using a small number of levels negatively effects on output voltage curve quality. Large assemblies already may be divided into smaller ones to be serviced and replaced independently. The article proposes an approach to development for an energy storage system not with a concentrated, but with a distributed battery where small battery assemblies are placed in the separate cell DC-link of a modular multilevel converter. A solution is also proposed that ensures the sensors minimization to ensure the possibility of accumulation and return of energy to the network.